Identifikasi Variasi Morfologi dan Kepadatan Kerang Bulu (Anadara antiquata) di Kabupaten Barru - Jafar, Jusmiati (Biology and Education Journal, 2023)
Anadara antiquata belongs to the Archidae family and class Bivalvia. Different environmental conditions can affect variations in morphology, population and density of an organism, especially shellfish. This study aims to identify variations in the morphology and density of seashells (Anadara antiquata) at Loji'e Beach, Bojo Village, Mallusetasi District, Barru Regency. The type of research used is descriptive quantitative. Sampling of seashells (Anadara antiquata) used the transect method (Line Transect Plot). Observations were made using 3 stations namely stations I, II, III with each station consisting of 5 plots with an interval of 10 m each plot with a plot size of 1x1m. analysis of morphological variation data using the morphometric method by observing the length, width and total weight of feather clams (Anadara antiquata), in density analysis using the formula density. The results of the research on the morphological variations of the shells (Anadara antiquata) found a variety of size variations, the differences in these variations were influenced by differences in temperature, salinity and pH of the water at the sample observation locations. Whereas for density analysis, different densities were found, the highest density was found at station 3 with a total of 30 individuals, this difference was influenced by differences in temperature, salinity and pH of the water where the clam (Anadara antiquata) lived.